Thermal treatment and properties of bovine hydroxyapatite - Niakan, A.; Ramesh, Singh; Abd Shukor, Mohd Hamdi; Jahanshahi, A.; Tan, C.Y.; Ching, Yern Chee; Tolouei, R. (Taylor & Francis, 2014)
Restoration process for damaged human bone may be performed using autograft, xenograft or allograft and alloplasts methods. Different bio-waste materials have been used as scaffolds for bone tissue engineering. Hydroxyapatite is a biomaterial that can be used as a bone graft material as it is similar to human bone and hard tissue. This work aims to characterise hydroxyapatite produced from the bovine bone at various temperatures from 400 to 700 degrees C. The microstructure and properties of a hydroxyapatite made by the sintering of bovine bone were examined by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy and infrared spectroscopy. The analyses indicated that the white sintered bone was hydroxyapatite and did not contain any organic components of the bone. X-ray diffraction patterns affirmed the phase condition and height of crystallinity level of the bovine hydroxyapatite obtained. Furthermore, phase transformation of the resulting hydroxyapatite to other calcium phosphate phases did not occur.